Green Human Resource Management and Its Importance Toward a Sustainable Workplace: A Comprehensive Literature Review - Akma, Yovi Faizul; Yasin, Nur; Perdhana, Mirwan Surya (Research Horizon, 2024)
The existing literature highlights Green Human Resource Management (GHRM) practices that influence organizational sustainability. This study examines GHRM's role in creating a sustainable workplace and its impact on performance. Achieving a sustainable workplace means balancing economic success with social and environmental responsibilities. This research uses a systematic review of studies on Green Human Resource Management (GHRM) and sustainable organizational performance. It includes articles published from 2018 to 2024 to ensure the findings are current and relevant. This research examines Green Human Resource Management (GHRM) and its impact on the three aspects of sustainability: economic, environmental, and social. It explains that economic sustainability involves incentives and reducing environmental impacts, social sustainability includes community involvement and equal opportunities, and environmental sustainability focuses on digital practices and educating employees on sustainability. Green Human Resource Management (GHRM) practices can make workplaces more sustainable and boost performance. HR managers are encouraged to use GHRM practices and other effective strategies to promote sustainability in their organizations.